2005
DOI: 10.1179/crn.2005.042
|View full text |Cite
|
Sign up to set email alerts
|

Trifid Mandibular Condyle: A Case Report

Abstract: A suspected case of trifid mandibular condyle that was observed on a panoramic radiograph and confirmed using computed tomography (CT) is reported. No history of previous temporomandibular joint (TMJ) trauma was reported by the subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…In both instances, there was trauma to the head and neck. In the third case, no potential cause of the TMC could be identified [3]. Our patient had been involved in a traffic accident resulting in trauma to the facial region at the age of 11 years.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In both instances, there was trauma to the head and neck. In the third case, no potential cause of the TMC could be identified [3]. Our patient had been involved in a traffic accident resulting in trauma to the facial region at the age of 11 years.…”
Section: Discussionmentioning
confidence: 95%
“…Coincidentally discovered, asymptomatic cases have also been reported [1,3,4,12]. In the three reported cases of TMC, the clinical findings ranged from slight deviation of the mandible to severe mandibular micrognathia with restricted mouth opening [1][2][3].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although the most common possible aetiology has been considered as trauma, comparative studies showed that the majority of patients had no history of previous trauma or TMJ complaints. 21,31,46 We found only four cases of trifid mandibular condyle in the literature (Artvinli and Kansu, 30 Antoniades et al, 31 Cagirankaya and Hatipoglu, 47 Sezgin and a b Tetrafid mandibular condyle Kayıpmaz 48 ). Three of the four reported cases of trifid mandibular condyle had history of trauma.…”
Section: Discussionmentioning
confidence: 89%
“…En ambos estudios, todos los pacientes negaron historia previa de trauma. La ocurrencia de cóndilo mandibular trífido es aun más rara, siendo apenas dos casos relatados en la literatura (Artvinli & Kansu, 2003;Cagirankaya & Hatipoglu, 2005).…”
Section: Discussionunclassified